2006
DOI: 10.1530/rep.1.01173
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilisation with frozen–thawed bovine sperm sexed by flow cytometry and validated for accuracy by real-time PCR

Abstract: The methodologies used for cytometric sorting of fresh spermatozoa never allowed a clear resolution of sexual chromosomes of frozen-thawed semen. To devise a novel method for the production of bovine predefined sexed embryos using frozen-thawed semen, sorting efficiency of different protocols was studied using a new quantitative real-time PCR method to verify the purity of sexed semen. To this aim, after Percoll separation, frozen-thawed samples were stained at different temperatures and concentrations of Hoec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 20 publications
1
19
0
2
Order By: Relevance
“…In vitro fertilization with sexed sperm has been approached with different sperm gradient separation techniques [6], modifying heparin concentrations, adding penicillamine, hipotaurine, and epinephrine (PHE) [7], or by means of new sperm cryopreservation procedures [8]. However, after fertilization with sex-sorted spermatozoa, lower fertility rates have been observed both in vivo [9 -13] (after AI) and in vitro [14 -16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro fertilization with sexed sperm has been approached with different sperm gradient separation techniques [6], modifying heparin concentrations, adding penicillamine, hipotaurine, and epinephrine (PHE) [7], or by means of new sperm cryopreservation procedures [8]. However, after fertilization with sex-sorted spermatozoa, lower fertility rates have been observed both in vivo [9 -13] (after AI) and in vitro [14 -16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ultrastructural studies showed that blastocysts produced with flow-cytometrically sexsorted spermatozoa have a lower quality than their nonsorted counterparts [19]. Puglisi and coworkers [6] described a minor tolerance of the sexed frozen-thawed sperm to the stress, making the manipulation procedures important during IVF. Although these kinetic and morphologic alterations may be responsible for the compromised development observed in embryos produced with sex-sorted spermatozoa, we could hypothesize that embryo development could be improved by using an optimized postfertilization culture.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the effect of some components found in Percoll, such as silica and PVP, which may have interfered with the DNA extraction process or amplification by qPCR, despite successive washes. There have been reports that Percoll at 80% concentration produced great variability during sexing sperm by flow cytometry (Stap et al, 1998;Puglisi et al, 2006). In the present study, centrifuged sperm were recovered in a fraction containing 90% Percoll, which theoretically could have affected qPCR results, as seen in sexing by flow cytometry.…”
Section: Discussionmentioning
confidence: 79%
“…However, OptiPrep was not effective to separate X sperm. The qPCR has recently been used as a reliable technique for the quantification of X and Y sperm cells in semen samples, especially to validate techniques for sexing sperm (Joerg et al, 2004;Parati et al, 2006;Puglisi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation